Variations in antibiotic susceptibility of group B Streptococcus in Japanese women: A long-term population-based cohort study - Yousuke Gomi; Liangcheng Wang; Hisashi Matsushima; Ayaka Kawabe; Atsuko Kikugawa; Akiyoshi Takagi; Kenichi Kuromaki (Elsevier, 2019)
Objective: To investigate the long-term antibiotic susceptibility of group B Streptococcus (GBS) present in the vagina. Materials and methods: A population-based retrospective cohort study was performed. A total of 19,899 women who underwent vaginal swab examination between 2005 and 2017 was enrolled. Specimens were cultured on modified Drigalski agar, blood agar, and chocolate agar media. Antibiotic susceptibilities of GBS were assessed using eight antibiotics, namely penicillin-G (PC-G), cefotiam (CTM), cefditoren (CDTR), ceftriaxone (CTRX), meropenem (MEPM), chloramphenicol (CP), levofloxacin (LVFX), and azithromycin (AZM), by the broth microdilution method when GBS was positive in the culture. The main outcome was antibiotic sensitivity based on the culture results. Results: GBS was 100% susceptible to PC-G, CTM, CTRX, CDTR, and MEPM. However, the susceptibility trend showed a considerable decrease for CP (99%-81%), LVFX (91%-70%), and AZM (87%-57%). Conclusions: Our study demonstrated a significant decrease in the antibiotic sensitivity of GBS in Japan in the past 13 years. Based on these results, current policies on antibiotic resistance of GBS in maternal and neonatal care may need to be reassessed. Keywords: Group B Streptococcus, Penicillin, Resistance, Streptococcus agalactiae, Susceptibility